2006
DOI: 10.1152/ajpregu.00838.2005
|View full text |Cite
|
Sign up to set email alerts
|

Physiological role of the α1- and α2-isoforms of the Na+-K+-ATPase and biological significance of their cardiac glycoside binding site

Abstract: An interesting feature of Na+-K+-ATPase is that it contains four isoforms of the catalytic alpha-subunit, each with a tissue-specific distribution. Our laboratory has used gene targeting to define the functional role of the alpha1- and alpha2-isoforms. While knockout mice demonstrated the importance of the alpha1- and alpha2-isoforms for survival, the knockin mice, in which each isoform can be individually inhibited by ouabain and its function determined, demonstrated that both isoforms are regulators of cardi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
93
0
3

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(98 citation statements)
references
References 59 publications
2
93
0
3
Order By: Relevance
“…*P Ͻ 0.05, **P Ͻ 0.001 vs. control (n ϭ 9 from 3 independent experiments). tracellular signal through the same molecule, the ␣-subunit of Na ϩ -K ϩ -ATPase (16,21). MBG and ouabain belong to two different subclasses of CTSs: bufadienolides, containing a five-membered lactone ring, and cardienolides with six-membered lactone, respectively.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…*P Ͻ 0.05, **P Ͻ 0.001 vs. control (n ϭ 9 from 3 independent experiments). tracellular signal through the same molecule, the ␣-subunit of Na ϩ -K ϩ -ATPase (16,21). MBG and ouabain belong to two different subclasses of CTSs: bufadienolides, containing a five-membered lactone ring, and cardienolides with six-membered lactone, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, elevated levels of endogenous CTSs including marinobufagenin (MBG) have been associated with various pathological conditions: essential hypertension (4,24,73), preeclampsia (3,45,83), experimental diabetes (7), uremic cardiomyopathy (33), and cardiac failure (20,48,49,66,74). MBG, like other CTSs, binds to the extracellular domain of the ␣-subunit of Na ϩ -K ϩ -ATPase (16,21), which, in addition to its well-known function of maintaining cellular electrochemical balance through pumping sodium and potassium ions, can act as a typical membrane receptor (14,28,35,55,56,73,74,84,85,88).…”
mentioning
confidence: 99%
“…5,6 The increased level of EO may have direct and indirect (via marinobufagenin) vasoconstrictor (hypertensive) effects by blocking sodium/potassium pump (Na þ /K þ -ATPase), consecutively increasing intracellular calcium level by the activation of the sodium-calcium exchanger, but this effect of EO is not homogenous, that is different Na þ /K þ -ATPase isoforms respond differently to EO. [7][8][9] Experimental use of low doses of ouabain increased arterial blood pressure in rats. 10 Beyond the classical effects of EO, the digitalis-like factors have genomic effects inducing hypertrophy in myocardial and vascular smooth muscle cells because of the activation of numerous known intracellular signaling pathways.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, there is good evidence that ␣2 plays an important role in contractility of vascular smooth muscle and control of blood pressure and regulation of Ca 2ϩ handling (23,24). Experiments with mice engineered to have ouabain-sensitive ␣1 and -insensitive ␣2 isoforms (␣1 S/S ␣2 R/R ) or ouabain-insensitive ␣1 and ␣2 (␣1 R/R ␣2 R/R ), instead of the wild-type with ouabain-insensitive ␣1 and ouabain-sensitive ␣2 (␣1 R/R ␣2 S/S ), have shown that ␣2 plays a predominant role in cardiac glycoside-induced positive inotropy (17,25) and also provide strong evidence for endogenous mammalian cardiac glycosides (25,26). ␣2 also plays the major role in cardiac glycoside-induced positive inotropy in rat cardiomyocytes (18).…”
mentioning
confidence: 99%